1998
DOI: 10.1111/j.1442-200x.1998.tb01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent hepatosplenomegaly and peripheral blood cytopenia, persistent Epstein‐Barr virus infection and central nervous system manifestation in a patient with lymphadenopathy and low serum uric acid

Abstract: Key wordsKENICHI SUGITA, SUSUMU HAGISAWA, YUHYA SATOH, MITSUOKl EGUCHI AND TOSHIHARU FURUKAWA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…These symptoms may even be typical of patients with EBV reactivation, as cognitive impairment, emotional instability, tiredness, dysarthria, and chorea were also observed among the 10 previously published patients with CNS disease due to EBV reactivation [Leavell et al, 1986;Tolly et al, 1989;Walter et al, 1989;Dagan and Shahak, 1993;Imai et al, 1993;Tachi et al, 1993;Morita and Tsuge, 1998;Sugita et al, 1998]. As in our patients, the laboratory findings of the cases reported were divergent, showing high anti-EA antibody titres in 6, positive blood PCR in 4, CSF or brain tissue PCR in 3, and AI in 3 cases.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These symptoms may even be typical of patients with EBV reactivation, as cognitive impairment, emotional instability, tiredness, dysarthria, and chorea were also observed among the 10 previously published patients with CNS disease due to EBV reactivation [Leavell et al, 1986;Tolly et al, 1989;Walter et al, 1989;Dagan and Shahak, 1993;Imai et al, 1993;Tachi et al, 1993;Morita and Tsuge, 1998;Sugita et al, 1998]. As in our patients, the laboratory findings of the cases reported were divergent, showing high anti-EA antibody titres in 6, positive blood PCR in 4, CSF or brain tissue PCR in 3, and AI in 3 cases.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, a search for acute primary EBV infections is well established in patients with central nervous system (CNS) diseases [Copperman, 1977;Weinstein, 1991;Cohen, 2000]. In contrast, neurological disease complicating the course of chronic active EBV infections [Shoji et al, 1992;Morita and Tsuge, 1998] or occurring in immunocompetent paediatric patients with reactivated EBV infections has been described only rarely [Leavell et al, 1986;Tolly et al, 1989;Walter et al, 1989;Dagan and Shahak, 1993;Imai et al, 1993;Tachi et al, 1993;Morita and Tsuge, 1998;Sugita et al, 1998]. …”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune neutropenia may present in previously healthy individuals (primary or idiopathic) or in patients with an underlying disease (secondary). It is mainly diagnosed in infancy and has been associated with viruses, such as Epstein-Barr virus and parvovirus B19 (25,26). In our study, an associated infectious agent (influenza B) was only identified in one case with autoimmune neutropenia.…”
Section: Discussionmentioning
confidence: 50%
“…As regards IM, the number of previous related studies is limited and the results are conflicting. A total of three early articles (16)(17)(18) with small number of recruited subjects and one previous case report (19) were retrieved. Dylewski et al (16) investigated 35 cases with IM after a case report, and reported that 7 men and 2 women had UA levels above the laboratory's upper limit of normal.…”
Section: Introductionmentioning
confidence: 99%
“…Cowdrey (17) reported UA elevation during the first 10 days of the disease course in 21 patients. However, Sugita et al (19) described a case of a 27-month-old boy with persistent EBV infection and CNS manifestations, who had lymphadenopathy and low UA levels. LI ZHANG 1* , PINGPING ZHOU 2* , ZHAOWEI MENG 2 , LU GONG 1 , CHONGJIE PANG 1 , XUE LI 2 , QIANG JIA 2 , JIAN TAN 2 , NA LIU 2 , TIANPENG HU 2 , QING ZHANG 3 , QIYU JIA 3 and KUN SONG 3 Departments of 1 Therefore, the aim of the present study was to analyze the associations between UA and IM in a comprehensive manner, in order to determine whether low UA is a significant risk factor for IM, and whether there is a sex difference.…”
Section: Introductionmentioning
confidence: 99%